The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/eos.12363
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the involvement of the macrophage migration inhibitory factor–glucocorticoid regulatory dyad in the expression of matrix metalloproteinase‐2 during periodontitis

Abstract: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine and counter-regulator of endogenous glucocorticoids. It is implicated in acute and chronic inflammatory diseases. This study investigated the role of the MIF-glucocorticoid (GC) regulatory dyad in MMP2 expression and release during periodontitis in vivo and in vitro. In a MIF knockout (KO) mouse model of ligature-induced periodontitis, gingival tissues and blood were collected and analyzed for levels of IL6, MIF, MMP2 and corticosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
1
12
1
Order By: Relevance
“…1). These data indicate that MIF mRNA expression appeared to be upregulated in the periradicular lesion induced in mice, corresponding to our previously published report, demonstrating that expression of MIF mRNA as well as its protein level are elevated in the experimental periodontitis induced in mice by ligature attachment (21).…”
Section: Expression Of Mif Mrna In a Mouse Periradicular Lesionsupporting
confidence: 91%
See 2 more Smart Citations
“…1). These data indicate that MIF mRNA expression appeared to be upregulated in the periradicular lesion induced in mice, corresponding to our previously published report, demonstrating that expression of MIF mRNA as well as its protein level are elevated in the experimental periodontitis induced in mice by ligature attachment (21).…”
Section: Expression Of Mif Mrna In a Mouse Periradicular Lesionsupporting
confidence: 91%
“…Although a plethora of studies has demonstrated the pathogenic roles of MIF, a variety of medical complications, such as heart failure, type two diabetes, and rheumatoid arthritis in the past decades (48)(49)(50)(51), and MIF's role in the bone pathophysiology remains controversial. Our group and others reported that MIF promotes osteoclastogenesis in vitro and upregulates the pathogenic bone resorption in various mouse models of osteolytic lesions (16,19,21). However, one research group reported that MIF deficiency inhibits both osteoclast and osteoblast activities without changing the numbers of osteoblasts or osteoclasts and reduces the bone mass in the context of homeostatic bone remodeling (42,52).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Excessive inflammation of the periodontal tissues (periodontitis) is the hallmark feature of PD. In PD, bacteria in the oral biofilm interfere with the body's defense mechanisms, activating the immune system which in turn results in inflammation and the immune response [17,18]. The levels of C-reactive protein, prostaglandin E 2 interleukin-1beta, and tumor necrosis factor alpha increase in PD [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified MIF overexpression in GCF from subjects with gingivitis [23], in gingival tissue from subjects with CP, in serum and tissue of mice with induced periodontitis [15, 30]. In addition, it has been described that MIF gene polymorphism ( MIF -173 G/C) increased the risk of CP [31].…”
Section: Discussionmentioning
confidence: 99%